Exploring Perceived Organizational Support To Improve Account Officer Performance - Muhammad Andi Prayogi; Jufrizen; Muhammad Fahmi; Muhammad Irfan Nasution (Jurnal Manajemen, 2022)
The purpose of this study was to identify Perceived Supervisor Support, Quality of Work Life on the performance of Account Officers with Perceived Organizational Support mediation. Data were collected from account officers of Islamic banking in North Sumatra as many as 385 respondents. The data analysis technique uses Structural Equation Modeling with SmartPLS. The results showed that Perceived Supervisor Support, Perceived Organizational Support affect performance, Quality of Work Life has no effect on performance and Perceived Organizational Support, Perceived Supervisor Support has an effect on Perceived Organizational Support, Perceived Organizational Support is an intervening variable between the influence of Perceived Supervisor Support on performance, and Perceived Organizational Support is not an intervening variable between the effect of Quality of Work Life on Account Officer performance. This study contributes to a greater understanding of the mediating role of perceived Perceived Organizational Support on the relationship between Perceived Supervisor Support, Quality of Work Life. Originality This research explores the mediation of Perceived Organizational Support between Perceived Supervisor Support and, Quality of Work Life on Performance, and Perceived Supervisor Support and Perceived Organizational Support are important antecedents in improving Account Officer performance.